HUBUNGAN RIWAYAT BERAT BADAN LAHIR RENDAH (BBLR) DAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI UPT PUSKESMAS KRAGILAN DESA KRAGILAN KABUPATEN SERANG BANTEN - Nurul Hidayah (2023)
Stunting is a form of growth failure (growth faltering) due to the accumulation of nutritional inadequacies that last for a long time which is influenced by many factors, there are direct and indirect factors. This study aims to analyze the relationship of history of low birth weight babies (LBW) and exclusive breastfeeding with the incidence of stunting in toddlers. This study used a cross sectional design with total sampling of 101 respondents. The sample in this study were all mothers who had children aged 24-59 months in the area of UPT Puskesmas Kragilan Kragilan Village Serang Regency Banten. The instruments used in the study were primary data direct measurement of children's height using a stadiometer and questionnaire sheets. Data analysis used in this study was univariate and bivariate statistical tests. The results of the bivariate test Chi-Square test in this study indicate that there is a relationship between LBW history and the incidence of stunting in toddlers with a value (P value = 0.000) with a value (OR 14.8, CI 3.579-61.206) meaning that a history of low birth weight babies has a 14.8 times greater risk of experiencing stunting than toddlers who are born normal or not LBW. This study also found that there was no relationship between exclusive breastfeeding history and the incidence of stunting in toddlers (P value = 0.331). From these results, researchers expect mothers to meet nutritional intake during pregnancy and continue to provide exclusive breastfeeding for 6 months to fulfill toddler nutrition during the golden period for more optimal growth.